2015
DOI: 10.3233/jpi-2010-0245
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant Klebsiella pneumoniae in NICU – what next? Trend of antibiotic resistance

Abstract: Multidrug resistant (MDR) Klebsiella pneumoniae an increasing cause of neonatal sepsis in India. This observational study was designed to monitor temporal change in prevalence of K. pneumoniae as a causative organism for neonatal sepsis and its sensitivity pattern. The time period was divided into four time frames of six months each [designated A (1/10/2006?31/03/2007) to D (1/04/2008?30/09/2008)]. K. pneumoniae isolation in all cultures sent from neonatal intensive care units doubled in time frame D (6.3%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…27 A similar resistance pattern was reported by Tagare et al The latter group reported 100% resistance to ampicillin and third-generation cephalosporins, almost 90% resistance to piperacillin and 40% resistance to carbapenems. 9 In the present study, overall the isolates had better susceptibility to piperacillin with tazobactam, amikacin, and ciprofloxacin. Nevertheless, it would seem inappropriate to use higher-generation broad-spectrum antibiotics in suspected sepsis cases that are not critically ill.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…27 A similar resistance pattern was reported by Tagare et al The latter group reported 100% resistance to ampicillin and third-generation cephalosporins, almost 90% resistance to piperacillin and 40% resistance to carbapenems. 9 In the present study, overall the isolates had better susceptibility to piperacillin with tazobactam, amikacin, and ciprofloxacin. Nevertheless, it would seem inappropriate to use higher-generation broad-spectrum antibiotics in suspected sepsis cases that are not critically ill.…”
Section: Discussionsupporting
confidence: 50%
“…An earlier report from western India also showed a similar pattern with gram-negative organisms accounting for more than 75% of the isolates. 9 Data from developing countries are more or less similar with K. pneumoniae as the major pathogen. 4 S. aureus emerged as the second most common organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 128 articles at the time of writing, none of which were preprints, were analyzed ( S1 Dataset ). The 128 articles comprised a total study population of 127,583 neonates in 30 countries of Africa ( n = 10; Algeria [ 27 ], Egypt [ 28 , 29 ], Ghana [ 30 ], Guinea [ 31 ], Morocco [ 32 , 33 ], Nigeria [ 34 37 ], South Africa [ 38 45 ], Tanzania [ 46 ], Tunisia [ 47 ], and Zambia [ 48 ]), Asia ( n = 10; Bangladesh [ 34 , 49 ], China [ 50 – 92 ], India [ 34 , 93 113 ], Iran [ 114 ], Israel [ 115 ], Japan [ 116 ], Nepal [ 117 ], Pakistan [ 34 , 118 – 122 ], Saudi Arabia [ 123 , 124 ], and Vietnam [ 125 128 ]), Europe ( n = 8; France [ 129 ], Greece [ 130 ], Hungary [ 131 ], Italy [ 132 142 ], Portugal [ 143 ], Russia [ 144 ], Turkey [ 145 147 ], and the United Kingdom [ 148 ]), and South America (Colombia [ 149 152 ] and Venezuela [ 153 ]) ( Fig 2 ). Among the ...…”
Section: Resultsmentioning
confidence: 99%
“…Compounding the difficulty and complexity of treating neonatal sepsis is antimicrobial resistance (AMR); as antibiotic use has increased and broader spectrum antibiotics are used more frequently, AMR has risen (4). Previously published longitudinal data from our neonatal intensive care unit (NICU) in western India from 2006 to 2008 already showed a worrying increase in multidrug-resistant (MDR) infection over the 2-year study period as well as persistently high rates of cephalosporin and carbapenem resistance (5). A more recent systematic review from 2019 on AMR in neonatal sepsis in South Asia (including 69 studies from India) shows that these challenges are ongoing and more widespread (6).…”
Section: Introductionmentioning
confidence: 99%